Chronic aryl hydrocarbon receptor activity phenocopies smoking‐induced skeletal muscle impairment. Issue 1 (1st November 2021) - Thome, Trace; Miguez, Kayla; Willms, Alexander J.; Burke, Sarah K.; Chandran, Vijayendran; de Souza, Angela R.; Fitzgerald, Liam F.; Baglole, Carolyn; Anagnostou, Maria‐Eleni; Bourbeau, Jean; Jagoe, R. Thomas; Morais, Jose A.; et al.
Abstract: Background: Chronic obstructive pulmonary disease (COPD) patients exhibit skeletal muscle atrophy, denervation, and reduced mitochondrial oxidative capacity. Whilst chronic tobacco smoke exposure is implicated in COPD muscle impairment, the mechanisms involved are ambiguous. The aryl hydrocarbon receptor (AHR) is a ligand‐activated transcription factor that activates detoxifying pathways with numerous exogenous ligands, including tobacco smoke. Whereas transient AHR activation is adaptive, chronic activation can be toxic. On this basis, we tested the hypothesis that chronic smoke‐induced AHR activation causes adverse muscle impact. Methods: We used clinical patient muscle samples, and in vitro (C2C12 myotubes) and in vivo models (mouse), to perform gene expression, mitochondrial function, muscle and neuromuscular junction morphology, and genetic manipulations (adeno‐associated virus‐mediated gene transfer). Results: Sixteen weeks of tobacco smoke exposure in mice caused muscle atrophy, neuromuscular junction degeneration, and reduced oxidative capacity. Similarly, smoke exposure reprogrammed the muscle transcriptome, with down‐regulation of mitochondrial and neuromuscular junction genes. In mouse and human patient specimens, smoke exposure increased muscle AHR signalling. Mechanistically, experiments in cultured myotubes demonstrated that smoke condensate activated the AHR, caused mitochondrial impairments, and induced an AHR‐dependent myotube atrophy. Finally, to isolate the role of AHR activity, expression of a constitutively active AHR mutant without smoke exposure caused atrophy and mitochondrial impairments in cultured myotubes, and muscle atrophy and neuromuscular junction degeneration in mice. Conclusions: These results establish that chronic AHR activity, as occurs in smokers, phenocopies the atrophy, mitochondrial impairment, and neuromuscular junction degeneration caused by chronic tobacco smoke exposure.